HERBAL USE EDUCATION FOR HEALTH IN THE COMMUNITY OF MUEANG DISTRICT KHON KAEN THAILAND - Silawati, Vivi; Widowati , Retno; Indrayani , Triana; Lomrah, Siti; Puteri , Aquarini Pajriyanti; Oktaviani , Lusi; Utami, Siti Puteri (Yayasan Education and Social Center, 2025)
Many community members do not know enough about herbs' benefits and how to use them properly, which often leads to distrust of their effectiveness as an alternative treatment. The habit of consuming modern medicines is more dominant than herbs. This is triggered by the perception that modern medicine provides results faster. Limited access to information about the types of herbs and their benefits and restricted access to quality herbal products in some areas. In 2024, 56 PCIM members studied in Thailand, and around 130 Indonesian students studied internationally at Khoen Kaen University (KKU). Around 40% of these students experienced physical complaints such as colds, nausea, vomiting and dizziness due to physical conditions, weather and other factors. The use of herbs/herbal medicine to maintain health and treat various diseases has been passed down from generation to generation. This legacy is expected to continue to be utilized by the younger generation, especially international students, as an alternative to increase endurance and overcome physical complaints. Indonesia and Thailand have similarities in using herbs as medicine, including ginger, melon, nutmeg, cinnamon, chilli, cloves, galangal, lemongrass, honey, and others. Community service was implemented in Mueang District, Khon Kaen, Thailand, on August 28, 2024, with 20 participants. After counselling and practice in making herbal drinks, participants learned the types, benefits and processing of spices to make herbal drinks that can be used as safe and effective alternative medicine.